Fatty acids profiling reveals potential candidate markers of semen quality. (27th September 2016) - Zerbinati, C.; Caponecchia, L.; Rago, R.; Leoncini, E.; Bottaccioli, A. G.; Ciacciarelli, M.; Pacelli, A.; Salacone, P.; Sebastianelli, A.; Pastore, A.; Palleschi, G.; Boccia, S.; et al.
Summary: Previous reports showed altered fatty acid content in subjects with altered sperm parameters compared to normozoospermic individuals. However, these studies focused on a limited number of fatty acids, included a short number of subjects and results varied widely. We conducted a case–control study involving 155 patients allocated into four groups, including normozoospermia ( n  = 33), oligoasthenoteratozoospermia ( n  = 32), asthenozoospermia ( n  = 25), and varicocoele ( n  = 44). Fatty acid profiling, including 30 species, was analyzed by a validated gas chromatography (GC) method on the whole seminal fluid sample. Multinomial logistic regression modeling was used to identify the associations between fatty acids and the four groups. Specimens from 15 normozoospermic subjects were also analyzed for fatty acids content in the seminal plasma and spermatozoa to study the distribution in the two compartments. Fatty acids lipidome varied markedly between the four groups. Multinomial logistic regression modeling revealed that high levels of palmitic acid, behenic acid, oleic acid, and docosahexaenoic acid (DHA) confer a low risk to stay out of the normozoospermic group. In the whole population, seminal fluid stearic acid was negatively correlated ( r  = −0.53), and DHA was positively correlated ( r  = 0.65) with sperm motility. Some fatty acids were preferentially accumulated in spermatozoa and the highest difference was observed for DHA, which was 6.2 times higher in spermatozoa than in seminal plasma. The results of this study highlight complete fatty acids profile in patients with different semen parameters. Given the easy‐to‐follow and rapid method of analysis, fatty acid profiling by GC method can be used for therapeutic purposes and to measure compliance in infertility trials using fatty acids supplements.